Eyeson: um arcabouço para extração, armazenamento e acompanhamento de métricas de projeto de circuitos integrados - Thiago Sousa Figueiredo Silva (2011)
We propose the usage of information obtained from conguration management tools stored data to track integrated circuit design evolution. The tracking is performed by the tool EyesOn. It is an open source framework designed to be extensible and to have easy integration with conguration management tools. The framework kernel architectureis composed by classes that represent handled entities and also store metrics and history information. We also present a set of product and process metrics gathered from design implementation, test and synthesis. In order to contextualize the problem a case study is presented. We prepared a development environment where university students developed a processor for academical purposes and sent development data to conguration management tools. After data extraction, some charts and an error proneness indication mechanism, based on temporal locality, are presented. Development history information has been already used to improve software productsand their development processes. We propose that in same direction this kind of information can be also applied to hardware. The information gathered from each design process step can be used to reduce bugs before fabrication and also to improve design process quality.